Palestinian identity in Jordan and Israel : the necessary 'other' in the making of a nation - Nasser, Riad M., 1950- (Middle East studies (Routledge (Firm)), 2005)
This study examines the process of national identity formation. It argues that national discourse are systems of meanings in which identities develop via difference.